Social Media Literacy's Impact on Entrepreneurial Interest Among Secretarial Students with Digital Financial Literacy Moderation - Reni Hariyani; Tio Prasetio (Universitas Bina Sarana Informatika, 2025)
Social media platforms offer numerous benefits to entrepreneurs; however, paradoxically, younger generations, such as university students, often fail to leverage these platforms to foster entrepreneurial interest. Additionally, financial management skills are essential for running a business effectively. This situation necessitates the development of social media literacy and digital financial literacy to enhance entrepreneurial interest among students. The purpose of this study is to analyze the influence of social media literacy on the entrepreneurial interest of secretarial program students and to investigate the moderating role of digital financial literacy in the relationship between social media literacy and entrepreneurial interest. This study employed a quantitative research approach, utilizing online questionnaire distribution as the primary data collection method. The sample was determined through purposive sampling involving 50 secretarial program students at Universitas Budi Luhur. The findings reveal that social media literacy has a positive and significant impact on the entrepreneurial interest of secretarial program students at Universitas Budi Luhur. Furthermore, the results indicate that digital financial literacy plays a role in shaping the effect of social media literacy on entrepreneurial interest among these students.